Stigma of poverty. The discursive construction of «South» term in Latin American countries - Gómez-Quintero, Juan David; Franco-Martínez, Juan Agustín (Iberoamerican Journal of Development Studies, 2013)
This article reflects a general knowledge and a macro-paradigmatic contribution of developmentalist discourses, in particular, its modernist and Eurocentric roots. In particular we analyze the artificiality of the discursive construction of certain categories that represent geopolitical stigma of poverty, such as Third World® or South® or underdeveloped® adopted in the field of international relations and the development cooperation. It notes that there are not metaphors opposite (North-South) in its own right, the "South" is not the opposite of the North®, but its negative extension, as evidenced by the imaginarium of most Latin American countries. The metaphors that stigmatize poverty are symbolic discourse used to define in a European way the identity of the winner (rich) peopleCITE AS:Gómez-Quintero, J.D., Franco-Martínez, J. A. (2014). Estigmas de la pobreza. La construcción discursiva del “Sur” en Latinoamérica. Iberoamerican Journal of Development Studies, 3 (1): 84-102
Keywords: Development; postcolonialism; Latin American countries; poverty